Experimental Investigation of Premixed LPG-Air Emission Profile During Flame Impingement Process - Israq, Imam; Nuryadin, Shakti; Sentanuhady, Jayan (Department of Mechanical and Industrial Engineering, 2024)
In the present study, emission profile of premixed 90% propane-10% butane flame, namely LPG (Liquified Petroleum Gas) was experimentally investigated. The fuel was mixed in premixed chamber which then ignited through 2 mm nozzle diameter. The fuel flow was controlled via solenoid valve installed upstream the burner body. This valve is synchronized with high-speed camera and thus, the flame kernel propagation can be captured. In this experiment, the effect of equivalence ratio, initial pressure, and separation distance (H/D) on combustion emissions and flames that produced from a mixture of LPG-air fuel was investigated. The flue gas analyser probe was installed inside the contained flame impingement test allowing to record CO, CO2, and unburnt HC data. The variation of the equivalence ratio used in this study are 0.8, 1.0, and 1.2. For variations in initial pressure used, 1 bar, 1.2 bar, and 1.4 bar. Variation of separation distance (H/D) that will be used are 4.5, 5.5, and 6.5. The result of this experiment shows that CO increases with increase in equivalence ratio, and initial pressure of premixed gas. For separation distance CO level decreases as the plate progressively moves away from the nozzle. CO and CO2 concentration increases as the equivalence ratio and initial pressure increases. The highest average CO concentration was 183 ppm that was found in ER 1.2 with the lowest H/D. Highest mean CO2 concentration was found in the same ER with the highest H/D, which was 4267 ppm.